Insecure about how to rate your job insecurity? A two-study investigation into time frames applied to job insecurity measures - Debus, Maike; Greulich, Berit; Kleinmann, Martin; König, Cornelius J. (Occupational Health Science, 2019)
Job insecurity is typically assessed via self-reports, with items usually being generic and non-contextualized (e.g., “I am sure I can keep my job”). Yet, such items may leave substantial room for interpretation, thus potentially individually biasing construct measurement. To test this, we added a time marker as a frame of reference to job insecurity items in Study 1. In a between-subjects design, participants completed a job insecurity measure under three conditions: near future-focused (i.e., job insecurity was rated with regards to the next sixth months), far future-focused (i.e., next five years), and unframed (i.e., no time reference). In the unframed condition we also asked participants which time frame they had in mind while completing the survey. Results showed that individuals’ job insecurity increased with longer time frames. In Study 2, we assessed common correlates of job insecurity and asked individuals about the time frame they had in mind when thinking about job insecurity as well as their reasons for this choice. Employees who chose longer time frames reported higher commitment, lower turnover intentions, lower psychological health complaints, and higher tenure. Qualitatively analyzing respondents’ reasons for selecting a particular time frame indicated that they either referred to time frames that were determined by their organization or politics, time frames that were determined by their position, individually predictable time frames, or individual time frames regarding professional development. Thus, giving items a frame can impact people’s stressor ratings, which implies that future job insecurity research should employ clear time frames
Keywords: frame of reference; contextualization; job insecurity; stressor perception